2022
DOI: 10.3390/su142114125
|View full text |Cite
|
Sign up to set email alerts
|

Are Consumers Aware of Sustainability Aspects Related to Edible Insects? Results from a Study Involving 14 Countries

Abstract: In recent years, edible insects have been suggested as an alternative food that is more sustainable compared with other sources of animal protein. However, knowledge about the sustainability aspects associated with this source of food may play a role in convincing consumers to adopt insects as part of their diet. In this context, the present study investigated the level of knowledge about the sustainability of edible insects in a group of people originating from 14 countries, with some naturally entomophagous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 63 publications
(101 reference statements)
1
14
0
Order By: Relevance
“…The results also show that gender, income and education level were associated with the awareness level of the spatial planning tools for disaster risk reduction. The male respondents being more aware of spatial planning tools is supported by past studies [52,53]. In addition, the study found out that informal settlers with low incomes and low educational levels [54,55] showed low levels of awareness of spatial planning tools and are therefore more exposed to the possibility of loss of life and destruction of property [54].…”
Section: Discussionsupporting
confidence: 62%
“…The results also show that gender, income and education level were associated with the awareness level of the spatial planning tools for disaster risk reduction. The male respondents being more aware of spatial planning tools is supported by past studies [52,53]. In addition, the study found out that informal settlers with low incomes and low educational levels [54,55] showed low levels of awareness of spatial planning tools and are therefore more exposed to the possibility of loss of life and destruction of property [54].…”
Section: Discussionsupporting
confidence: 62%
“…Participants who ate insects out of curiosity, a desire to protect the environment, a desire to enjoy eating insects, and because of their nutritional value were those with relevant knowledge. These findings evidently demonstrate that a number of variables have a significant influence on people's knowledge of the sustainability of edible insects, which may be helpful in formulating strategies to spread awareness and eventually boost people's willingness to consider edible insects as a serious alternative to other protein foods, even in nations that are not accustomed to them (Guiné et al, 2022).…”
mentioning
confidence: 85%
“…Besides, a study by van Huis et al (2013) revealed that edible insect harvesting, and collection can provide job opportunities and generate income at both household and industrial scale of processing. Guiné et al (2022) reported that the edible insect market in the Asia-Pacific region is forecasted to surpass US $270 million by 2024. Even though more than half of the market is currently dominated by Asia-Pacific and Latin America, the most significant growth is anticipated in North America and Europe due to the increasing market demand of edible insects for human consumption.…”
Section: Traditional Market Of Edible Insectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parametric tests were used for data that presented a normal distribution (according to the Kolmogorov–Smirnov test) [ 25 ]. The tests used were the t -test for independent samples to compare between two groups and Analysis of Variance—ANOVA, complemented with a post hoc Tukey test to identify the differences between three or more groups [ 26 ].…”
Section: Methodsmentioning
confidence: 99%